Functional Importance of Transient Receptor Potential (TRP) Channels in Neurological Disorders - Lee, Kihwan; Jo, Youn Yi; Chung, Gehoon; Jung, Jung Hoon; Kim, Yong Ho; Park, Chul-Kyu (Frontiers in Cell and Developmental Biology, 2021)
Transient receptor potential (TRP) channels are transmembrane protein complexes that play important roles in the physiology and pathophysiology of both the central nervous system (CNS) and the peripheral nerve system (PNS). TRP channels function as non-selective cation channels that are activated by several chemical, mechanical, and thermal stimuli as well as by pH, osmolarity, and several endogenous or exogenous ligands, second messengers, and signaling molecules. On the pathophysiological side, these channels have been shown to play essential roles in the reproductive system, kidney, pancreas, lung, bone, intestine, as well as in neuropathic pain in both the CNS and PNS. In this context, TRP channels have been implicated in several neurological disorders, including Alzheimer’s disease, Parkinson’s disease, Huntington’s disease, amyotrophic lateral sclerosis, and epilepsy. Herein, we focus on the latest involvement of TRP channels, with a special emphasis on the recently identified functional roles of TRP channels in neurological disorders related to the disruption in calcium ion homeostasis.